Rare Case of Isolated Right Sided Dilated Cardiomyopathy: Right Sided Dilated Cardiomyopathy (GAIMS Journal of Medical Sciences, 2022)
In dilated cardiomyopathies biventricular involvement is the usual case though left ventricular dysfunction is more apparent. In RVDCM, as the name suggests right ventricle is solely involved and left ventricular function is normalThe other causes of right heart failure are tricuspid valve disease (infective endocarditis, rheumatic, Ebsteins anomaly), right ventricular infarction and rarely pulmonary regurgitation without pulmonary hypertension. The diagnosis was made on echocardiography which revealed dilated, hypokinetic right ventricle, with normal left ventricular dimensions and ejection fraction and no evidence of pulmonary artery hypertension with normal pulmonary artery size and normal pulmonary valve with dilated right ventricle outflow tract